Association of nutritional status, plasma, albumin levels and pulmonary function in cystic fibrosis Asociación entre el estado nutricional, niveles de albúmina plasmática y función pulmonar en pacientes con fibrosis quística - M. I. Souza dos Santos Simon; M. Drehmer; F. A. de Abreu e Silva; A. Hoffmann; C. Druck Ricachinewsky; E. de Fonseca Andrade Procianoy; I. Scattolin; S. Saldanha Menna Barreto (Nutrición Hospitalaria, 2011)
Background & aims: Malnutrition is related with pulmonary disease. The aim was to analyze the association of lung function respectively to nutritional status, identified pulmonary pathogens and socioeconomic condition of patients attending a pediatric CF reference center. Methods: Cross-sectional study performed with CF patients aged 6 to 18 years attending a CF-Center in southern Brazil. Nutritional status, plasma albumin level and pulmonary bacterial colonization were assessed. The outcome studied was forced expiratory volume in 1 second (FEV1). Results: Eighty-five patients were included in this study. FEV1 was significantly associated with body mass index (BMI) percentiles, plasma albumin level and methicillin resistant Staphylococcus aureus (MRSA) pulmonary colonization. Regression analysis showed that BMI below the 10th percentile was associated with a 25.58% drop in FEV1, and plasma albumin levels equal to or lower than 4.1 mg/dL was associated with 18.6% FEV1 reduction. FEV1 was 14.4% lower in the MRSA infected patients. Plasma albumin of 4.25 mg/dL predicted FEV1 of 60% with 76.9% sensitivity and 72.2% specificity, and 85.7% accuracy. The socioeconomic status was not association with pulmonary function. Conclusion: BMI below the 10th percentile and albumin below 4.1 mg/dL were predictors of low FEV1. Chronic MRSA infection was associated with lower FEV1. Longitudinal studies may better complement these results. Objetivos: Analizar la asociación entre la función pulmonar y tres factores: el estado nutricional, el estado de patógenos pulmonares y el estado socio-económico de pacientes en un centro de referencia en atención a pacientes pediátricos con fibrosis quística. Métodos: Se realizó un estudio longitudinal en pacientes con fibrosis quística, de 6 a 18 años atendidos en un centro de fibrosis quística del Sur del Brasil. Fueron evaluados: estado nutricional, niveles de albúmina plasmática y colonización bacteriana pulmonar. El principal resultado estudiado fue el volumen espiratorio forzado en el 1 segundo (FEV1). Resultados: Fueron incluidos en este estudio 85 pacientes. El FEV1 se mostró significativamente correlacionado con percentiles del Índice de Masa Corporal (IMC), albúmina plasmática y colonización pulmonar por Staphylococcus aureus resistente a meticilina (SARM). El análisis de regresión mostró que el IMC abajo del percentil 10 estuvo asociado con una disminución del 25,58% en el FEV1, y que niveles de albúmina plasmática iguales o menores a 4,1 mg/dL se correlacionaron on una reducción de 18,6% del FEV1. El FEV1 fue 14,4% menos en los pacientes infectados por SARM. La albúmina plasmática de 4,25 mg/dL predijo un FEV1 de 60% con una sensibilidad de 76,9% una especificidad de 72,2% y precisión de 85,7%. El estado socioeconómico no tuvo asociación con la función pulmonar. Conclusiones: El IMC debajo del percentil 10 y albúmina plasmática menor que 4,1 mg/dL fueron predictivos de un bajo FEV1 . La infección crónica de SARM mostró asociación con un menor FEV1.